2004
DOI: 10.1103/physrevb.70.020405
|View full text |Cite
|
Sign up to set email alerts
|

Chiral mixed phase in disordered3dHeisenberg models

Abstract: Using Monte Carlo simulations, we compute the spin stiffness of a site-random 3d Heisenberg model with competing ferromagnetic and antiferromagnetic interactions. Our results for the pure limit yield values of the the critical temperature and the critical exponent ν in excellent agreement with previous high precision studies. In the disordered case, a mixed "chiral" phase is found which may be in the same universality class as 3d Heisenberg spin glasses.PACS numbers: 64.70. Pf, 75.40.Gb, 75.40.Mg The critic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
0
19
2
Order By: Relevance
“…A theoretical model of random magnets constructed by random substitution of magnetic ions is a site-random model. 12,13,15,16,[20][21][22][23][24][25][26] Regarding a binary magnetic alloy, we can describe a site-random model with two types of magnetic ions, A and B. In this model, A and B ions are placed randomly on the lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical model of random magnets constructed by random substitution of magnetic ions is a site-random model. 12,13,15,16,[20][21][22][23][24][25][26] Regarding a binary magnetic alloy, we can describe a site-random model with two types of magnetic ions, A and B. In this model, A and B ions are placed randomly on the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The Heisenberg model using this decision rule of interactions for all directions on a three-dimensional lattice has been investigated using Monte Carlo simulations. 12,13,15,16 This model can be considered as a fundamental model of isotropic materials. However, we cannot adapt this model in the present case because origins of interaction depend on the direction in the infinite-layer structure treated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…6 They concluded that four ordering scenarios were possible although none could be ruled out. In addition, we 2 and others 7,8 have suggested that the ordering within the mixed phase might not be characterized by the Heisenberg universality class of the parent model although a consistent picture has yet to emerge. We have recently determined phase diagrams for the site frustrated Heisenberg model on three different lattices, 2 one of which ͑simple cubic͒ is shown in Fig.…”
mentioning
confidence: 66%
“…Such magnetic systems with disordered atomic distributions have been of considerable theoretical and experimental interest for many years [8][9][10][11][12]. Disorder can lead to a competition between two order parameters and hence phases having exotic behaviors such as spin glass and mixed ordering [13][14][15][16][17][18]. The siterandom Heisenberg model is thought to capture the essential physics of such systems [17].…”
Section: Introductionmentioning
confidence: 99%